General and subspecialist pediatrician perspectives on barriers and strategies for referral: a latent profile analysis - James C. Bohnhoff; Katherine Guyon-Harris; Kelsey Schweiberger; Kristin N. Ray (BMC, 2023)
Abstract Background Children in need of pediatric subspecialty care may encounter multiple barriers, and multiple strategies have been suggested to improve access. The purpose of this study was to describe the perceptions of general and subspecialty pediatric physicians regarding barriers to subspecialty care and the value of strategies to improve subspecialty access. Methods We surveyed a national sample of 1680 general pediatricians and pediatric subspecialists in May and June 2020 regarding 11 barriers to subspecialty care and 9 strategies to improve access to subspecialty care, selected from recent literature. Using latent profile analysis, respondents were grouped according to the degree to which they believed each of the barriers impacted access to subspecialty care. Using chi-squared tests, we compared the profiles based on respondent characteristics and perspectives on strategies to improve access. Results The response rate was 17%. In 263 responses completed and eligible for inclusion, the barriers most frequently described as "major problems" were wait times (57%), lack of subspecialists (45%) and difficulty scheduling (41%). Respondents were classified into 4 profiles: "Broad concerns," "Subspecialist availability concerns," "Clinician communication concerns," and "Few concerns." These profiles varied significantly by respondent specialty (p < .001, with medical subspecialists overrepresented in the "Clinician communication" profile, psychiatrists in the "subspecialist availability" profile, and surgeons in the "few concerns" profile); and by respondents' typical wait time for appointments (p < .001, with physicians with the longest wait times overrepresented in the "subspecialist availability" profile). Conclusions We found specific profiles in clinician views regarding barriers to subspecialty care which were associated with perspectives on strategies aimed at overcoming these barriers. These results suggest that health systems aiming to improve subspecialty access should first identify the barriers and preferences specific to local clinicians.